Colony stimulating factor-1 regulation of macrophages in development and disease - Stanley, E. Richard (Henry Stewart Talks, 2009)
Colony stimulating factors, Action of CSF-1 and its isoforms, The CSF-1 receptor (CSF-1R) and its new ligand, IL-34, CSF-1 and the CSF-1R in mouse models of inflammatory disease and cancer, A proteomic approach CSF-1R signaling, Action of the downstream signaling molecule, PSTPIP2, PSTPIP2 mutations cause autoinflammatory disease, A genetic approach to CSF-1R structure/function and signaling, Current questions